Завдання Служби безпеки України як суб’єкта захисту державного суверенітету та територіальної цілісності - Бережной, С. М.; Berezhnoi, S. M. (Держава та регіони. Серія: Право. – 2023. – № 2 (80). – С. 326-330, 2023)
Зазначено, що діяльність Служби безпеки України як суб’єкта захисту державного суверенітету та територіальної цілісності протидіє злочинам, що становлять найбільшу суспільну небезпеку та посягають на: національну безпеку; конституційний лад; територіальну цілісність; інформацію, яка може зашкодити державним інтересам і національній безпеці. Запропоноване власне бачення завдань Служби безпеки України як суб’єкта захисту державного суверенітету та територіальної цілісності, які полягають у здійсненні профілактичній, контррозвідувальній, охоронній діяльності в сфері національної безпеки, запобіганні та протидії правопорушенням пов’язаними з: поваленням конституційного ладу, насильницькими змінами кордонів країни, державною зрадою та іншими подібними діями, несанкціонованим використанням інформації з обмеженим доступом, особливо у сфері оборони; незаконним перетином кордонів країни суб’єктами та переміщення через ці кордони об’єктів, у тому числі наркотичних засобів, психотропних речовин, їх аналогів чи прекурсорів; організацією та фінансуванням тероризму, зокрема з використанням зброї масового знищення або шляхом геноциду чи екоциду; пропагандою та веденням війни; образою чи погрозою життю представників державних органів і іноземних держав; піратством і найманством.

The article states that the activity of the Security Service of Ukraine as a subject of protection of state sovereignty and territorial integrity counteracts crimes that pose the greatest public danger and encroach on: national security; constitutional order; territorial integrity; information that may harm state interests and national security. For its part, territorial integrity is an integral component of state sovereignty, and therefore the tasks of the Security Service of Ukraine to protect these values are essentially joint. At the same time, it is clear that the competence of the Security Service of Ukraine is not limited to preventing and countering certain categories of crimes, ensuring the security of strategically important objects, etc. An equally important direction is counterintelligence activity - a special direction of work aimed at prevention, timely detection and prevention of external and internal threats to the security of Ukraine, termination of intelligence, terrorist and other illegal encroachments by special services of foreign states, as well as organizations, individual groups and individuals on the state security of Ukraine, elimination of the conditions that contribute to them and the causes of their occurrence. In conclusion, the author proposed his own vision of the tasks of the Security Service of Ukraine as a subject of protection of state sovereignty and territorial integrity, which consist in the implementation of preventive, counter-intelligence, security activities in the field of national security, prevention and countermeasures of offenses related to: overthrowing the constitutional order, violent changes in the borders of the country, treason and other similar actions, unauthorized use of information with limited access, especially in the field of defense; illegal crossing of the country's borders by subjects and movement of objects across these borders, including narcotic drugs, psychotropic substances, their analogues or precursors; organization and financing of terrorism, in particular with the use of weapons of mass destruction or through genocide or ecocide; propaganda and warfare; an insult or threat to the life of representatives of state bodies and foreign countries; piracy and mercenary.

Отмечено, что деятельность Службы безопасности Украины как субъекта защиты государственного суверенитета и территориальной целостности противодействует преступлениям, представляющим наибольшую общественную опасность и посягающим на: национальную безопасность; конституционный строй; территориальную целостность; информацию, которая может нанести ущерб государственным интересам и национальной безопасности. Предложено собственное видение задач Службы безопасности Украины как субъекта защиты государственного суверенитета и территориальной целостности.
Tasks of the Security Service of Ukraine as a subject of protection of state sovereignty and territorial integrity
Keywords: державний суверенітет; територіальна цілісність; Служба безпеки України; завдання; протидія злочинності; антитерористична діяльність; державна таємниця; state sovereignty; territorial integrity; Security Service of Ukraine; task; countering crime; anti-terrorist activity; state secret; государственный суверенитет; территориальная целостность; Служба безопасности Украины; противодействие преступности; антитеррористическая деятельность; государственная тайна